THE QUALITY OF GOAT MEAT STORED AT COLD TEMPERATURE - da Costa, Iolanda Hermenegildo; Agustina, Kade Karang; Swacita, Ida Bagus Ngurah (Buletin Veteriner Udayana, 2022)
This study aims to determine the quality of goat meat stored at a cold temperature of 4°C in terms of subjective test, objective test and eber test. This study used a completely randomized split-in-time design with storage treatment at a cold temperature of 4°C with 5 observations, namely on day 1, 2, 3, 4, 5 each observation was examined for 5 samples. This study used local goat meat on the thigh as much as 200 grams from 5 different goats, then stored at a cold temperature of 4°C and tested for quality by subjective test, objective test and eber test. The results showed that goat meat stored at a cold temperature of 4°C had significant differences in color, odor, consistency, texture, pH, water content, water holding capacity and Eber's test (P<0.05). The results of the organoleptic test of mutton stored at a temperature of 4°C were shown by a change in the color of the meat to pale red, the smell of the meat becoming slightly fishy and foul-smelling, the consistency of the meat becoming mushy and the texture of the meat turning rough starting from the 4th day, on the results of the objective test, there was a decrease in pH, an increase in water content and a decrease in water holding capacity as well as a positive eber test result and the meat experienced early spoilage on the 4th day. the quality of goat meat is decreasing.